Attitudes of Dentistry Students at the UAM-Xochimilco Towards Their Professional Training - Sáenz Martínez, Laura; Sánchez Pérez, Leonor; Luengas Aguirre, Isabel; Jarillo Soto, Edgar (Education Policy Analysis Archives, 2007)
The purpose of this article is to analyze the attitudes of students towards the theoretical and clinical knowledge and about research as part of the Dentistry Program during their professional training at the Universidad Autónoma Metropolitana-Xochimilco. A questionnaire with Likert items was applied to students in order to know their answers about these topics. An X2 test was applied to analyze the homogeneity of answers. Results indicate that students’ opinions differ on: a) the amount of theoretical content regarding treatment (p < .003), b) some aspects regarding clinical knowledge (p < .006), and c) research options per school year (p < .05). We conclude that it is necessary to study in depth the achievements and limitations of the program proposed by the Universidad Autónoma Metropolitana-Xochimilco.